Introduction to Human Osteology - Hall, Roberta; Beals, Kenneth; Neumann, Holm; Neumann, Georg; Madden, Gwyn (Open textbook library., 2010)
This text was designed for use in the human osteology laboratory classroom. Bones are described to aid in identification of skeletonized remains in either an archaeological or forensic anthropology setting. Basic techniques for siding, aging, sexing, and stature estimation are described. Both images of bone and drawings are included which may be used for study purposes outside of the classroom. The text represents work that has been developed over more than 30 years by its various authors and is meant to present students with the basic analytical tools for the study of human osteology.